Beyond Cultural Parodies and Parodizing Cultures: Shaping A Discourse (American Journal of Islam and Society, 1991)
Contrasting Epistemics“why if a fish came to me and told me he was going on a journey, I shouldsay, With what porpoise?”’ “Don’t you mean burpose’?” said Alice.“I mean what I say,” the Mock Turtle replied in an ofended tone.(Lewis Carroll, Alice in Wonderland)Consider this analogy: There was a man beneath a tree. He wished to collecthis thoughts, but the sparrows disturbed him with their chirping. He wouldchase them with his stick and then resume his train of thought, but the sparrowswould come back and he would have to scare them away. . . Eventuallysomeone told him: %is is like being a slave at the wheel going round andround forever. Ifyou want to escape the vicious circle, you shouldfell the tree:Imam al Ghazali,(Ihya’ ‘Ulum al Din)Cultural Parodies: Shaping a DiscourseAbstractIt has been the practice for the dominant paradigm to set the terms ofrational discourse and for the “Other” to defer in reverence - if it wanted tobe admitted to the circle of respectability. In this case, the tables are turnedMOM Abul-Fadl directs the Research Project on Western Thought at the InternationalInstitute of Islamic Thought, Herndon, Virginia and is the chairperson of the Political ScienceDiscipline Council of the Association of Muslim Social Scientists.and the dominant paradigm, which is secularist, is viewed critically throughthe lens of a re-emerging tawhidi paradigm. The purpose is not to engagein a test of will or vision, but to lay the ground for a discourse which canaccommodate a genuine diversity-in-dignity for all, and which would includeSelf and Other in a re-formed world of inter-relatedness developed throughnew categories and points of reference. In a common human heritage richin communicable symbols and transitive experiences, cultivating the termsof a hermeneutic of mutuality is imminent. Its objectives would be to redefineand assure worldly morality and rationality at higher levels of reality. Onlythen can the self-imposed constraints, constrictions, and anomalies whichare inherent in the prevailing culture be transcended. The context for shapingthis discourse can be as broad and encompassing or as concrete and particularas the response in the concurrent fields of the humanities and the social scienceswill admit ...